Pengembangan dan Evaluasi Efek Antioksidan serta Peningkatan Energi dari Minuman Cokelat Berbasis Ekstrak Tart Cherry pada Atlet Muda - Athirah Khanayah Hud; Aditya Pratama Putra; Selvany Asti Aprianti; Arif Widatama (An-Najat, 2025)
This study developed and evaluated the effects of a tart cherry extract-based chocolate drink on young athletes. The background addresses the high oxidative stress and fatigue hindering athletic recovery. Using a double-blind, randomized controlled trial, 30 young athletes were divided into an intervention group (consuming the tart cherry chocolate drink) and a control group (placebo) for 14 days during intensive training. Parameters measured included total antioxidant capacity (TAC), malondialdehyde (MDA) levels, rating of perceived exertion (RPE), and recovery time. Results indicated that the intervention group showed a significant increase in TAC and a decrease in MDA levels compared to the control. Furthermore, the intervention group reported lower RPE scores and faster recovery times post-exercise. It was concluded that the tart cherry-based chocolate drink effectively enhances antioxidant status, reduces oxidative stress, and supports energy recovery in young athletes, positioning it as a promising functional nutritional supplement.